2019
DOI: 10.1001/jamacardio.2019.0084
|View full text |Cite
|
Sign up to set email alerts
|

Survival Differences in Women and Men After Septal Myectomy for Obstructive Hypertrophic Cardiomyopathy

Abstract: IMPORTANCE Recent data indicate that women with hypertrophic cardiomyopathy (HCM) are older and more symptomatic at presentation and have worse clinical outcomes than men. However, to our knowledge, there are no large studies of the association of patient sex with outcomes after surgical myectomy. OBJECTIVE To analyze preoperative characteristics and overall survival of women and men undergoing septal myectomy for obstructive HCM. DESIGN, SETTING, AND PARTICIPANTS This retrospective, single-center study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 37 publications
9
35
0
1
Order By: Relevance
“…Geske et al [8] reported a large number of female patients undergoing ASA and an independent association of female sex with worse long-term survival. However, Meghji et al [9] reported similar outcomes for women and men with HOCM after surgical myectomy. It is not well understood whether there are sex disparities in long-term outcome in symptomatic patients with HOCM undergoing ASA, especially in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 94%
“…Geske et al [8] reported a large number of female patients undergoing ASA and an independent association of female sex with worse long-term survival. However, Meghji et al [9] reported similar outcomes for women and men with HOCM after surgical myectomy. It is not well understood whether there are sex disparities in long-term outcome in symptomatic patients with HOCM undergoing ASA, especially in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 94%
“…Potential sex differences concerning survival after myectomy have been investigated by several studies [5,16,17]. A recent study by Meghji et al on 2506 patients demonstrated worse survival in women in their unadjusted analysis [16]. However, this difference was not found after adjustment for baseline characteristics.…”
Section: Sex Differencesmentioning
confidence: 99%
“…В ряде крупных исследований, в которых анализи ровались данные пациентов с ГКМП, также как и в на шем исследовании, отмечено, что женщины были стар ше, имели более выраженные клинические проявления и ЭхоКГ признаки диастолической дисфункции, нужда лись в более интенсивном наблюдении и раннем рассмо трении хирургической тактики [3,4]. Нарушение про цессов релаксации миокарда у больных ГКМП может быть связано как с мутационными изменениями сокра тительных белков кардиомиоцитов и развитием гипер трофии, так и с увеличением фиброза.…”
Section: Discussionunclassified